Impact of Gardening on Physical and Mental Health in The Midst of Covid-19 Pandemic - Merrychelle Bebs P. Coyoca; May-Ann B. Del Rosario; Jean Rose L. Lazo; Vivencio L. Calixtro Jr.; Lilibeth B. Edaño (Indonesian Journal of Community and Special Needs Education, 2022)
The study aimed to determine the impact of gardening on the physical and mental health amidst pandemics. The study employed a descriptive design and the survey questionnaire was used for gathering data. There were 60 respondents with ages of 18 to 65 years old who are residing in Barangay Maibo, Tantangan South Cotabato. The gathered data were treated using a statistical tool such as mean, frequency, and percentage. The study revealed that the impact of gardening on physical health strongly agreed with the grand mean of 4.22 and the mental health was agreed with the grand mean of 4.10. Based on the findings, it is concluded that gardening has an impact on physical and mental health. The researchers highly recommend conducting programs for people to avoid anxiety and depression. The students are also encouraged to engage themselves in gardening to boost their physical and mental health.